How Informal Education Fosters Economic Awareness in Children - Rahmatullah, Rahmatullah; Inanna, Inanna; Ampa, Andi Tenri (Dinamika Pendidikan, 2020)
The research aimed to find out how the education pattern in the family forms children's economic awareness. Qualitative descriptive was used as an approach in this study to reveal how the role of farmer families in the Maritengngae sub-district, Sidrap Regency in fostering economic awareness in their children. The number of informants in this study was 10 people. The data collection used observation, documentation, and interviews. The results showed that economic education was part of education that took place in the family environment to foster economic awareness in children from an early age through habituation, exemplary and transfer of knowledge. The characteristics of economic education in the family can be seen in various aspects, namely giving verbal advice, participating in shopping, and habituation in saving, limiting pocket money, and priority scale in fulfilling needs. The role of housewives is very important in fostering habits and role models in children from an early age with the hope that in the future they will become responsible economic actors.